Umbilical reconstruction: different techniques, a single aim - Gardani, Marco; Palli, Dante; Simonacci, Francesco; Grieco, Michele Pio; Bertozzi, Nicolò; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2019)
Summary. The umbilicus is a unique physiologic scar of human life resulting from the healing process of the cut umbilical cord at birth. Its absence leads to an unnatural abdominal appearance, and an abnormally shaped or misplaced umbilicus may draw undue attention to the central abdomen. Loss of the umbilicus can be an embarrassing deformity; this occurs when older techniques of umbilical hernia or incisional hernia repair are employed and after abdominoplasty, urachal cyst repair, omphalocele repair, gastroschisis repair, some tumor excisions, and mobilization of bipedicled or bilateral TRAM/DIEP flaps for breast reconstruction. Umbilicoplasty, in which the umbilicus remains anchored to the deep abdominal fascia but is transposed through a newly-formed aperture in the upper abdominal skin flap, is performed in abdominoplasty either for abdominal flap harvest or purely for aesthetics. On the other hand, umbiliconeoplasty describes the de novo creation of an umbilicus that is absent for either congenital or acquired reasons. The optimal umbilical reconstruction should be reliable, reproducible, aesthetically appropriate, and associated with low morbidity. Ideally, it is also single-staged, except in the case of an infected wound, in which case a delayed primary approach may be prudent. (www.actabiomedica.it)